Development of acute parotitis after non-invasive ventilation - Martinez, Eduardo; Dicpinigaitis, Peter V. (Journal of Thoracic Disease, 2017)
A 90-year-old woman underwent laparoscopic exploratory laparotomy for evaluation of suspected mesenteric ischemia. She was promptly extubated postoperatively and transferred to the intensive care unit, where on the first postoperative day she developed hypoxemia necessitating initiation of noninvasive ventilation (NIV) with bilevel positive airway pressure (BiPAP). After 8 hours of BiPAP, she was noted to have swelling, erythema and tenderness in the right preauricular area. Ultrasound evaluation demonstrated an enlarged right parotid gland. With discontinuation of BiPAP and supportive measures, parotitis resolved within 6 days. The mechanism of NIV-induced acute parotitis likely involves transmission of positive pressure to the oral cavity, causing obstruction to salivary flow within the parotid (Stensen) duct. Conditions that increase salivary viscosity and promote salivary stasis, such as advanced age, dehydration, and absence of salivary gland stimulation due to restriction of oral intake, may render patients more susceptible to this complication. As NIV will continue to be a commonly-used modality for the treatment of acute respiratory failure, clinicians should be aware of this phenomenon.